NEW AND ADDITIONAL RECORDS OF GABRIUS STEPHENS, 1829 (COLEOPTERA: STAPHYLINIDAE: STAPHYLININAE) FROM TURKEY AND CYPRUS - Ozgen, Inanc; Khachikov, E. A. (Inst Bioloska Istrazivanja Sinisa Stankovic, 2013)
In this study, 10 species of Gabrius are recorded from Turkey and Cyprus. Amongst these, five species are first records: Gabrius bulgaricus Coiffait, 1971 and G. hissaricus Schillhammer, 2003 from Turkey; G. nigritulus (Gravenhorst, 1802) and G. ravasinii Gridelli, 1920 from Cyprus.
Keywords: Coleoptera; Staphylinidae; Staphylininae; Gabrius; Turkey; Cyprus; new records